E-voting jako forma demokracji bezpośredniej. Dotychczasowe doświadczenia i ich konsekwencje - Duda, Krzysztof (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
This article is going to point main advantages and disadvantages of e-voting. That form of voting could be a turning point in modern democracy. It can avoid many concerns and problems – there are some certain examples attached. It’s our choice to try e-votig but it’ is essencial to know all pros and cons